Pengaturan Impor Paralel dalam Merek (Studi Perbandingan Hukum Indonesia, India dan New Zealand) - Lewinsky Cai (Journal of Law and Policy Transformation, 2020)
Parallel import is a concept for importing and reselling original products from distributors that are legally obtained from producers at lower prices rather than buying directly from producers. These products are placed on the market in one country with the approval from owner and imported to another country without the permission of the owner. Parallel imports are built on the principle of exhaustion of rights. Basically, there are three principles of exhaustion of rights, namely;the principle of international exhaustion of rights, domestic/national exhaustion of rights and regional exhaustion of rights. Based on the TRIPS agreement, each country is given the freedom to determine and regulate the principle of exhaustion of rights to be applied. The issue under discussion is how the parallel import regulation in brands according to Indonesia, Indian, and New Zealand laws what can be adopted in Indonesia law regarding parallel imports based on these comparisons. In this study, the writer used a normative research method. This research also uses legal comparison as part of its analysis with data collection techniques through literature study. Data analysis method used is descriptive qualitative method. The results of the study showed that Indonesia has no regulation regarding parallel imports. While in India and New Zealand there are related regulations. Regarding disputes settlement regarding parallel imports in Indonesia, civil law is adopted, in India with a judge's decision in accordance with existing regulations. What can be adopted by Indonesia in this case is to explicitly reinforce regulations regarding parallel imports in brands.